2019
DOI: 10.4149/bll_2019_129
|View full text |Cite
|
Sign up to set email alerts
|

Nod-like receptor protein 3 and nod-like receptor protein 1 inflammasome activation in the hippocampal region of postmortem methamphetamine chronic user

Abstract: OBJECTIVE AND BACKGROUND: Methamphetamine (Meth) is one of the most important central nervous system (CNS) stimulant abuse drugs that cause long-term or permanent damage to different regions of the brain, particularly hippocampus, by neuronal apoptosis and infl ammation. In this study, we evaluated Nodlike Receptor Protein 3(NLRP3) and Nod-like Receptor Protein1 (NLRP1) Infl ammasome Activation in the Hippocampal Region of postmortem Meth Chronic User. METHODS: Molecular and histological analyses were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Neuroinflammation is a major underlying mechanism of methamphetamine (METH)-induced cognitive deficits. Increased levels of hippocampal NLRP1 and NLRP3 inflammasome expression as well as the induction of inflammation and apoptosis were found in 11 patients with METH drug use disorder [ 110 ]. METH promotes NLRP inflammasome release, and upregulates caspase-1 expressions, causing the aggregation of apoptosis-associated ASC proteins from rat cortical microglial.…”
Section: Roles Of Nlrp Inflammasome In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Neuroinflammation is a major underlying mechanism of methamphetamine (METH)-induced cognitive deficits. Increased levels of hippocampal NLRP1 and NLRP3 inflammasome expression as well as the induction of inflammation and apoptosis were found in 11 patients with METH drug use disorder [ 110 ]. METH promotes NLRP inflammasome release, and upregulates caspase-1 expressions, causing the aggregation of apoptosis-associated ASC proteins from rat cortical microglial.…”
Section: Roles Of Nlrp Inflammasome In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Consequently, "tolerance" to the ORF-1 mRNA-increasing effect of METH may be due to accelerated decrease in these RNAs. Chronic METH can induce apoptosis and cell death in the hippocampus [27,85]; therefore, it is also possible that ORF-1 mRNA decreased in this brain region, due to the accelerated death of cells containing ORF-1 mRNA during chronic treatment with METH.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, emerging evidence has emphasized the combined roles of NLRP1 and NLRP3 in the CNS ( 147 , 148 ), especially in brain injury ( 24 , 146 , 149 ). Moreover, a report showed that high levels of NLRP1 and NLRP3 were present in the hippocampus of patients abusing methamphetamine ( 150 ), indicating the relationship between these two classic inflammasomes and a promising strategy for the treatment of brain injury.…”
Section: Nlrp1 As a Target For The Treatment Of Brain Injurymentioning
confidence: 99%